Стратегија на текстилната индустрија за настап на глобалниот пазар - Иванов, Ристо (Економски факултет, УКИМ, Скопје, 2012)
This paper aims to elaborate the importance of strategic planning in order to improve companies’ and industries’ competitiveness for global market entry. The planned and clear process of defining global market strategy increases the chances for success within market contest. That is the reason why the more important industries implements strategic planning as response to challenge arose from globalization of markets and fierce competition. Textile industry in Republic of Macedonia faces the same challenges. The implementation of appropriate global market strategy has to be a response to restructuring processes of this industry in developed countries and to follow the integration processes’ trends. The maintenance and the increase Macedonian textile industry’s competitiveness on the global market are connected with strategic planning process and defined strategic goals. Data used from researches related to textile industry’s condition serves as base to assess the textile industry’s need to plan global market position and to realize importance of strategic management in order to improve its competitiveness. Theoretical knowledge about the phases of strategic management are explained and implemented for the purposes of textile industry in Republic of Macedonia. Within the work the research is carried out. It is about finding out managers’ considerations towards implementation of strategic management as a tool to improve competitiveness and their attitudes about perspectives of textile industry on the global market.
Textile Industry’s Strategy for Global Market
Докторска дисертација одбранета во 2012 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубомир Дракулевски.
Keywords: strategic planning, strategic menagment, strategy, global market, textile industry, competitiveness